THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND PEER GROUP WITH SELF-CARE AMONG HEMODIALYSIS PATIENTS IN RSI JEMURSARI SURABAYA - Yolanda Ivanka Putri; Lono Wijayanti; Wesiana Heris Santy; Nur Hidaayah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Surabaya, 2023)
Background: Patients who are undergoing hemodialysis must be able to take care of themselves, but the fact is that these patients often do not pay attention to what must be controlled and treated so that hemodialysis patients need support from their families and peer groups. Objective: The purpose of this study was to analyze the relationship between family and peer group support with self-care in hemodialysis patients at RSI Jemursari in Surabaya. Methods: This study used a quantitative design with correlation analytics with a cross sectional approach. The study population was all patients who were undergoing hemodialysis as many as 150 respondents. The sample obtained 109 respondents using simple random sampling. This independent variable is family support and peer group, the dependent variable is self-care. Data collection using a questionnaire was analyzed using the Spearman Rank test. Result: Based on the results of the study of 109 respondents, almost all (78%) received good family support, almost all (91.7%) received good peer group support and most (71.6%) had high self-care. Based on the results of the Spearman rank test, the value of p = 0.000 was obtained, which means that there is a relationship between family and peer group support with self-care in hemodialysis patients. Conclusion: The conclusion of this study, the higher the family and peer group support, the self-care in hemodialysis patients will also increase. Families and peer groups are expected to continue to provide support to individuals, thereby assisting individuals in maintaining self-care.